Echogenic Mass Lesion within the Main Pulmonary Artery in a Neonate - Lae-Eun Jeong; Jae Yoon Na; June Huh; I-Seok Kang; Ji-Hyuk Yang; Tae-Gook Jun; Jin Young Song (Korean Society of Neonatology, 2020)
Here we present a rare case of pulmonary arterial thrombosis associated with a ductus arteriosus aneurysm that caused severe pulmonary stenosis. A 5-day-old newborn was admitted to our hospital for the evaluation of an intracardiac mass-like lesion found after the detection of a cardiac murmur. Echocardiography and heart computed tomography revealed a mass-like lesion measuring 8.1 mm in diameter across the distal main pulmonary artery to the proximal left pulmonary artery resulting in localized severe stenosis of the left pulmonary artery. Left pulmonary artery angioplasty for surgical resection of the thrombus revealed that the mass was adherent to the proximal part of the left pulmonary artery anterior wall and extended to the ductus arteriosus. Histological examination of the mass showed an old thrombus with dystrophic calcification. Five months after surgery, follow-up echocardiography showed that the left pulmonary artery peak pressure gradient had decreased but the proximal left pulmonary artery stenosis remained. Cardiac catheterization and balloon angioplasty suc cessfully relieved the pulmonary stenosis.